QUARTET: A SIOP Europe project for quality and excellence in radiotherapy and imaging for children and adolescents with cancer. (September 2022) - Kelly, Sarah M.; Effeney, Rachel; Gaze, Mark N.; Bernier-Chastagner, Valérie; Blondeel, Anne; Clementel, Enrico; Corning, Coreen; Dieckmann, Karin; Essiaf, Samira; Gandola, Lorenza; Janssens, Geert O.; Kearns, Pamela R.; et al.
Abstract: The European Society for Paediatric Oncology (SIOPE) Radiation Oncology Working Group presents the QUARTET Project: a centralised quality assurance programme designed to standardise care and improve the quality of radiotherapy and imaging for international clinical trials recruiting children and adolescents with cancer throughout Europe. QUARTET combines the paediatric radiation oncology expertise of SIOPE with the infrastructure and experience of the European Organisation for Research and Treatment of Cancer to deliver radiotherapy quality assurance programmes for large, prospective, international clinical trials. QUARTET-affiliated trials include children and adolescents with brain tumours, neuroblastoma, sarcomas including rhabdomyosarcoma, and renal tumours including Wilms' tumour. With nine prospective clinical trials and two retrospective studies within the active portfolio in March 2022, QUARTET will collect one of the largest repositories of paediatric radiotherapy and imaging data, support the clinical assessment of radiotherapy, and evaluate the role and benefit of radiotherapy quality assurance for this cohort of patients within the context of clinical trials. Highlights: High-quality, protocol compliant radiotherapy is essential in clinical trials. QUARTET is a platform for centralised prospective radiotherapy quality assurance. QUARTET facilitates a strong collaborative network for paediatric radiation oncology. QUARTET improves equity in access to paediatric radiotherapy expertise across Europe. QUARTET supports central review of diagnostic imaging for treatment failure analysis.